Answer:
5a) 4
5b) 4
Explanation:
You'll use Pythagorean theorem throughout this problem a lot. So, to find X, You have a right triangle with one leg of 6, and one leg of 2. 2 squared plus 6 squared equals c squared. 4 + 36 = c squared then you get 40 = c squared.
To get c by itself you'd square root both sides. So that leaves you with X = the square root of 40.
Now, to get Y, you have another triangle with a leg of 4, and another leg of the square root of 40. 4 squared = 16, and the square root of 40 squared is just 40. So, 16 + 40 = c squared. 56 = c squared, then again, to get the c value by itself you need to square root both sides, leaving you with Y = the square root of 56.